IMPLEMENTASI APLIKASI PENGELOLAAN DATA PERALATAN DAN BAHAN LABORATORIUM PADA BALAI HIPERKES DAN KESELAMATAN KERJA PROVINSI KALIMANTAN SELATAN - Dwi Retnosari (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2019)
The Hiperkes Center of South Kalimantan Province is one of the Unit for Occupational Health Centers in the Province of South Kalimantan, one of its services is to conduct environmental testing in companies and the community. Balai Hiperkes Laboratory has a lot of tools and materials. So it is necessary to build an application so that the data management of the Equipment and Materials in the Laboratory becomes more effective and efficient. The Laboratory Equipment and Material Management System at the Hiperkes Center of South Kalimantan Province is still done manually. In conventional data processing with a data collection system that is now felt there are still many deficiencies that occur, because the existing system still uses sheets of paper, archives and uses Microsoft Office applications (MS-Word and MS-Excel) even using the Book archive, so that it can cause data is easily lost or damaged. System development in the form of Implementation of Desktop-Based Tools and Materials Data Management Application in Hiperkes Central Laboratory is a system that provides offline information in the form of reports on desktop and tool-based management data using the Delphi 7 application with MySQL database, thus helping speed and quality in submit information. Besides that, based on the desktop, the data information can be accessed with an unspecified time and place. In this system, it can only be accessed by the user or the lab admin. In this study, aside from describing the theoretical studies used as the basis for the preparation, it will also be discussed about system design and information system development. So that it is expected to be implemented in a product that will correct all the shortcomings that exist in the old system.